Waterpipe smoking: the pressing need for risk communication. (2nd November 2019) - Maziak, Wasim; Osibogun, Olatokunbo; Asfar, Taghrid
ABSTRACT: Introduction : Waterpipe (WP) smoking is an important public health problem that is rapidly evolving globally. Much of WP spread among youth is perpetuated by a misperception of reduced harms compared to cigarettes. Increasing awareness about WP smoking harms through health warning labels (HWLs) represents a promising policy and regulatory strategy to curb WP smoking. Areas covered : Peer-reviewed publications indexed in PubMed and CINAHL were searched in March 2019. This review focuses on the current knowledge of WP smoking characteristics, its spread and patterns of use globally, and some of the major WP-related health effects. This knowledge is utilized to advance a promising policy and regulatory avenue to curb WP smoking by increasing awareness of its potential harms through HWLs. It also addresses product configuration and unique features that influence the adaptation of HWLs for WP smoking. Expert opinion : HWLs are effective in communicating smoking-related risks to WP smokers in a way that affects their smoking behavior and experience as well as interest in quitting. Although based on limited data, the WP device appears to be a promising location for HWLs as it offers prolonged contact with smokers and those surrounding them.